2019
DOI: 10.1051/0004-6361/201935304
|View full text |Cite
|
Sign up to set email alerts
|

New light on the Gaia DR2 parallax zero-point: influence of the asteroseismic approach, in and beyond the Kepler field

Abstract: The importance of studying the Gaia DR2 parallax zero-point by external means was underlined by Lindegren et al. (2018), and initiated by several works making use of Cepheids, eclipsing binaries, and asteroseismology. Despite a very efficient elimination of basic-angle variations, a small fluctuation remains and shows up as a small offset in the Gaia DR2 parallaxes. By combining astrometric, asteroseismic, spectroscopic, and photometric constraints, we undertake a new analysis of the Gaia parallax offset for n… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(74 citation statements)
references
References 74 publications
(127 reference statements)
6
68
0
Order By: Relevance
“…Comparing Kepler first-ascent red giant branch and red clump asteroseismic parallaxes to Gaia DR2 parallaxes, Khan et al (2019) find agreement between the Gaia and asteroseismic radius scales within ∼ 5%. We note that our results are not directly comparable because they do not account for f ∆ν , and so their level of agreement between Gaia and asteroseismic radius scales is an upper bound.…”
Section: Scaling Relations For [Fe/h] < −1mentioning
confidence: 74%
“…Comparing Kepler first-ascent red giant branch and red clump asteroseismic parallaxes to Gaia DR2 parallaxes, Khan et al (2019) find agreement between the Gaia and asteroseismic radius scales within ∼ 5%. We note that our results are not directly comparable because they do not account for f ∆ν , and so their level of agreement between Gaia and asteroseismic radius scales is an upper bound.…”
Section: Scaling Relations For [Fe/h] < −1mentioning
confidence: 74%
“…By the study of a sample of RR-Lyrae, the parallax zero point was found to be 0.057±0.0034 mas Muraveva et al (2018) It is therefore undoubtable that there is a non-zero parallax offset in the Gaia DR2 between 0.2 and 0.8 mas. There is a significant difference in the parallax zero-points derived from fainter and bluer quasars (0.029 mas, Lindegren et al (2018)) and from brighter and redder sources like Cepheids (0.046 mas, Riess et al (2018); 0.048 mas, Groenewegen (2018)), RR Lyrae (0.057 mas, Muraveva et al (2018)), or red giants and red clump stars (0.0528 mas, Zinn et al (2019); 0.0517 mas, Khan et al (2019); and 0.03838 mas, Hall et al (2019)).…”
Section: Dmt Applicationmentioning
confidence: 99%
“…reported a parallax offset of 0.082±0.033 mas using a sample of eclipsing binaries. In 2019, many more studies dealt with the Gaia parallax zero point and the value varies between 0.030 and 0.1 mas (0.031±0.11mas,Graczyk et al (2019); 0.054±0.006mas,Schönrich et al (2019); 0.0523±0.002 mas,Leung & Bovy (2019); 0.075±0.029mas,Xu et al (2019); 0.0517±0.0008mas,Khan et al (2019); 0.03838 +0.01354 −0.01383 mas,Hall et al (2019); and 0.0528±0.0024 mas,Zinn et al (2019)).…”
mentioning
confidence: 99%
“…The zero-point offset between the observed and asteroseismic parallaxes is considered in many papers in the literature (Sahlholdt et al 2018;Zinn et al 2018;Khan et al 2019;Hall et al 2019). Most of these studies find the observed parallax less than the asteroseismic parallax: ∆π = π obs − πsis, about -0.05 mas.…”
Section: Comparison Of the Observed And Asteroseismic Parallaxesmentioning
confidence: 99%